High-occupancy toll lanes: Their distributional impact and effect on congestion - Jonathan Daines Hall (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper reports the theoretical and empirical evidence on the distributional effects of Express Lanes. It also provides evidence of how they affect congestion, both in the Express Lanes themselves and in the parallel general-purpose lanes. The paper also helps put Express Lanes in context by discussing the merits of alternative approaches to managing congestion such as ramp metering, permits, and vehicle-kilometres travelled charges.
Keywords: 330; Verkehrsstau; Vertriebsweg; Verkehrsverhalten; Transportzeit